2014
DOI: 10.6027/tn2014-531
|View full text |Cite
|
Sign up to set email alerts
|

The Nordic model – challenged but capable of reform

Abstract: TemaNord 2014:531The Nordic model -challenged but capable of reform Tarmo Valkonen and Vesa Vihriälä (eds.) Contributions by:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 67 publications
(76 reference statements)
0
5
0
Order By: Relevance
“…Unemployment ratio = unemployed 15-24 year-olds in relation to the whole population of the age group. Source: OECD as reproduced from Albaek et al (2014).…”
Section: Youth Unemploymentmentioning
confidence: 99%
See 3 more Smart Citations
“…Unemployment ratio = unemployed 15-24 year-olds in relation to the whole population of the age group. Source: OECD as reproduced from Albaek et al (2014).…”
Section: Youth Unemploymentmentioning
confidence: 99%
“…The red line shows the 45 degree angle. Source: OECD, as reproduced from Albaek et al (2014). Notes: Unemployment ratio = unemployed in relation to the whole population of the age group.…”
Section: Youth Unemploymentmentioning
confidence: 99%
See 2 more Smart Citations
“…In Finland, we know that the distribution of health and social welfare services and access to services are relatively good at the macro level (Pulkki et al, 2015;Vaarama et al, 2014;Valkonen et al, 2014). Even though most clients feel that the accessibility of social services is at a good level, some clients repeatedly reported that client payments were too expensive, services could not be accessed quickly enough, or there were other difficulties with the accessibility of services (Ilmarinen et al, 2016).…”
Section: Discussionmentioning
confidence: 99%